ALLERGIC CONTACT DERMATITIS - Tersinanda, Trisna Yuliharti; Mas Rusyati, Luh Made (E-Jurnal Medika Udayana; vol 2 no 8 (2013):e-jurnal medika udayana, 2013)
Normal 0 false false false EN-US X-NONE X-NONE Allergic contact dermatitis is an immunologic reaction that tends to involve the surrounding skin and may even spread beyond affected sites. This skin disease is one of the more frequent, and costly dermatologic problems. Recent data from United Kingdom and United States suggest that the percentage of occupational contact dermatitis due to allergy may be much higher, thus raising the economic impact of occupational allergic contact dermatitis. There is not enough data about the epidemiology of allergic contact dermatitis in Indonesia, however based on research that include beautician in Denpasar, about 27,6 percent had side effect of cosmetics, which is 25,4 percent of it manifested as allergic contact dermatitis. Diagnosis of allergic contact dermatitis is based on anamnesis, physical examination, patch test , and this disease should be distinguished from other eczematous skin disease. The management is prevention of allergen exposure, symptomatic treatment, and physicochemical barrier /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: allergic, occupation, contact dermatitis